1994
DOI: 10.1002/bip.360340208
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of trypsin digestion and conformational flexibility at different sites of unfolded lysozyme

Abstract: Fourteen tryptic peptides and nine intermediates were identified as products of trypsin digestion of reduced and S-3-(trimethylated amino) propylated lysozyme. Kinetics of the appearance and disappearance of these products were observed by monitoring the peak areas on the chromatogram. In spite of the complicated reaction pathways, kinetics of the digestion of proteins and several intermediate products show simple decay curves with a single rate constant. In this paper, the trypsin susceptibility of the indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…The latter interpretation appears as the only realistic one, based on the following considerations. (i) The rates measured for MxM and MϭM are 2-3 orders of magnitude lower than those reported in the literature for tryptic hydrolysis of proteins, folded or unfolded (21,22). Furthermore, when a preparation of S protein dissociated from S peptide was treated with trypsin under the same conditions employed for MxM and MϭM, a value of k hydrolysis ϭ 1,240 ϫ 10 Ϫ4 min Ϫ1 was measured.…”
Section: Limited Tryptic Proteolysis Of Bs-rnase and Of Its Isolatedmentioning
confidence: 73%
“…The latter interpretation appears as the only realistic one, based on the following considerations. (i) The rates measured for MxM and MϭM are 2-3 orders of magnitude lower than those reported in the literature for tryptic hydrolysis of proteins, folded or unfolded (21,22). Furthermore, when a preparation of S protein dissociated from S peptide was treated with trypsin under the same conditions employed for MxM and MϭM, a value of k hydrolysis ϭ 1,240 ϫ 10 Ϫ4 min Ϫ1 was measured.…”
Section: Limited Tryptic Proteolysis Of Bs-rnase and Of Its Isolatedmentioning
confidence: 73%
“…MALDI-TOF MS analysis of region 1 identified the protein as AGP or orsomucoid (Table 1). Due to the preferential action of trypsin [21] and less ionization efficiency of glycopeptides [22], the sequence coverage of some of the proteins were found to be less. In the present study it was observed that potential N-linked glycopeptides were not covered by PMF spectra and this may be reflected in low sequence coverage.…”
Section: Maldi-tof Ms Identification and Immuno-validation Of Proteinmentioning
confidence: 97%
“…Therefore, the early PHCm promoter is probably stronger than most, if not all, of the currently known early type promoters that can be expressed in recombinant baculoviruses. It has been shown that the unfolding of a protein may result in protease degradation (35,36), and improper protein modifications occur at a late stage of infection (37)(38)(39). These previous observations imply that the production of relatively lower quantity of protein with better activity may be the result of a relatively better folding or modifications on proteins generated by the early type PHCm promoter than those generated by the very late p10 promoter.…”
Section: Discussionmentioning
confidence: 99%